Anti-angiogenics: their role in the treatment of glioblastoma - Winkler, Frank; Osswald, Matthias; Wick, Wolfgang (Oncology research and treatment, 2018)
Angiogenesis is a hallmark of glioblastomas, but anti-angiogenic therapies have fallen short of the initial expectations to relevantly change the clinical course of the disease. Only one agent, the anti-vascular endothelial growth factor (VEGF)-A antibody bevacizumab, has shown meaningful efficacy in controlled clinical trials in glioblastoma, so far. In primary and recurrent glioblastoma, this efficacy is, however, limited to prolonging progression-free survival and to generating some additional palliative benefits, without affecting overall survival in the total population of glioblastoma patients. Here, we give an overview of the current status of anti-angiogenic therapy in glioblastoma, including how it is currently used in the clinic. Furthermore, we discuss avenues of biomarker research aiming to identify those glioblastoma patients with a higher likelihood of profiting from anti-VEGF-A therapies (and to identify those who will not). Together with novel anti-angiogenic treatment targets and combination regimens under development today, those might improve the current clinical benefits from this class of drugs in glioblastoma.